Progress in Oral Vaccination against Tuberculosis in Its Main Wildlife Reservoir in Iberia, the Eurasian Wild Boar - Beatriz Beltrán-Beck; Cristina Ballesteros; Joaquín Vicente; José de la Fuente; Christian Gortázar (Veterinary Medicine International)
Eurasian wild boar (Sus scrofa) is the main wildlife reservoir for tuberculosis (TB) in Iberia. This review summarizes the current knowledge on wild boar vaccination including aspects of bait design, delivery and field deployment success; wild boar response to vaccination with Bacillus Calmette-Guérin (BCG) and inactivated Mycobacterium bovis; and wild boar vaccination biosafety issues as well as prospects on future research. Oral vaccination with BCG in captive wild boar has shown to be safe with significant levels of protection against challenge with virulent M. bovis. An oral vaccination with a new heat-killed M. bovis vaccine conferred a protection similar to BCG. The study of host-pathogen interactions identified biomarkers of resistance/susceptibility to tuberculosis in wild boar such as complement component 3 (C3) and methylmalonyl coenzyme A mutase (MUT) that were used for vaccine development. Finally, specific delivery systems were developed for bait-containing vaccines to target different age groups. Ongoing research includes laboratory experiments combining live and heat-killed vaccines and the first field trial for TB control in wild boar.